Ordinary People on the Move: Subaltern Cosmopolitanisms in Amitav Ghoshâ€™s Writings - Roy, Indian Institute of Technology, Kharagpur, India, Anjali Gera (Asiatic: IIUM Journal of English Language and Literature, 2012)
This essay draws on Ulf Hannerzâ€™s notion of locals and cosmopolitans and Zygmunt Baumanâ€™s idea of the tourists and the vagabonds to focus on the movements of ordinary folks in Ghoshâ€™s works due to a number of reasons that equip them with an â€œorientation towards the otherâ€ (Berland 124). Borrowing Joseph Berlandâ€™s category of â€œmulti-service nomads,â€ it argues that his engagement with these movements anticipates the new discourse on cosmopolitanism and shows that in contrast to contemporary cosmopolitan narratives that privilege the movements of the new professional, intellectual or artistic elite, Ghosh recovers the buried narratives of those who may be called subaltern cosmopolitans even though their movements might have been triggered from above. After summarising contemporary understandings of cosmopolitanism as developed in the discourse of globalisation, the essay proceeds to uncover such cosmopolitanism that was produced through the contact zones created by trade, travel and indenturement.